M-Learning and Experiential Learning in Vocational Education - Luptáková, Iveta D.; Hanuliaková, Jana; Žido, Lukáš; Bartoš, Pavel (Emerging Science Journal, 2024)
The aim of our research was to investigate the impact of the use of mobile devices in mobile technology (MT)-enabled experiential learning (EL). Methods/Analysis: The basis of the research was an experiment. Quantitative data included pretest and post-test results of two groups of students (ELs and regular education students). Qualitative data consisted of individual analysis of a final questionnaire composed of 37 items, some of which were open-ended. A 5-point Likert scale was used for evaluation, and some questions were open-ended. Findings: The results showed that the average knowledge gained in the EL group's post-test increased compared to the regular class. We found that after the photographing/note-taking phase, students with the ability to use mobile devices generally lost interest in further observation. We also found that both groups had great difficulty in the question design and comparison sections, in finding answers to the prepared questions. Novelty/Improvement:it became apparent that the teaching process needed to be modified. The photo-taking phase should be done after close observation so that the sensory experience is not replaced by mobile devices. The comparison phase did not show a significant result in any of the observed viewpoints and can be omitted. The sensory experience, sound recording, requires some modifications, more effectively applied in the classroom environment, as ambient noise was a problem in the teaching process. Doi: 10.28991/ESJ-2024-SIED1-017 Full Text: PDF